ANALISIS SISTEM ANTRIAN PELAYANAN ADMINISTRASI PASIEN RAWAT JALAN PADA RUMAH SAKIT PADMALALITA MUNTILAN - Mimi Kurnia Nengsih; Mimi Vera Yustanti (Management Insight: Jurnal Ilmiah Manajemen, 2017)
The Issues raised in this research is: "How does the queuing system of administrative services outpatient hospital padmalalita Muntilan". The purpose of this study was to determine the queuing system administration services outpatients at the hospital padmalalita Muntilan. From the calculation of analytical performance Queue System with Single Change Single Phase (M / M / 1) arrival Patients most visible onvMonday, where the average patient comes highest in the hours 09:00 to 11:00, wherevthe average time patients spent waiting in patients with the necessary longest queue in the queue is 0.061 minutes and 0.009 minutes is the shortest time that happened in the hours 11:00 to 12:00. The longest time it takes the patient in the system is 1,111 minutes that occurred at 09:00 to 10:00 and 10:00 to 11:00 and shortest time is 0.059 minutes which occurred at 11:00 to 12:00.If the addition of the server into two servers, patient waiting time in the queue is reduced. The waiting time in the queue the longestvfor one server that is 0.061 minutes per patient, if using 2 servers waiting time was reduced to 0,004 minutes per patient.